The Lung in Hereditary Hemorrhagic Telangiectasia - Dupuis-Girod,S; Cottin,V; Shovlin,CL (Respiration, 2017)
Hereditary hemorrhagic telangiectasia (HHT) is a dominantly inherited genetic vascular disorder with an estimated prevalence of 1 in 6,000, characterized by recurrent epistaxis, cutaneous telangiectasia, and arteriovenous malformations (AVMs) that affect many organs including the lungs, gastrointestinal tract, liver, and brain. Its diagnosis is based on the Curaçao criteria, and is considered definite if at least 3 of the 4 following criteria are fulfilled: (1) spontaneous and recurrent epistaxis, (2) telangiectasia, (3) a family history, and (4) pulmonary, liver, cerebral, spinal, or gastrointestinal AVMs. The focus of this review is on delineating how HHT affects the lung.